Establishment of Cladonia stellaris after artificial dispersal in an unfenced forest in northern Sweden - Roturier, Samuel; Bergsten, Urban (Rangifer, 2009)
In 2002, fragments and whole thalli of reindeer lichen, mainly Cladonia stellaris, were spread in a typical Scots pine forest in northern boreal Sweden to study the survival and development after artificial lichen dispersal. The forest was not fenced, allowing reindeer access to graze. Lichens were dispersed in intact vegetation in 1 m2 plots by one of two methods: either as an intact lichen mat (patch) of 0.25 m2 in the centre of the plot or as fragments scattered (scatter) across the whole plot. The lichen was then monitored by photo inventory. In 2006, three years after the first inventory, all patch plots had been partially grazed by reindeer and the lichen cover measured in both patch and scatter plots had decreased severely. In 2008, the lichen cover in the patch and scatter plots had increased by up to 54% and 88%, respectively, of the cover measured during the first inventory in 2003. A significant increase in the number of fragments in the plots was also observed between 2006 and 2008, suggesting that in addition to growing like naturally established thalli, the lichen had spread and slowly colonized the plots. Dispersing lichen by the “patch” method appears to be less costefficient than the “scatter” method, if the area is grazed by reindeer. These results support the hypothesis that dispersal of reindeer lichen could be an effective means of restoring lichen stands, which are important for reindeer husbandry, even if the area is open to reindeer grazing. Abstract in Swedish / Sammanfattning: Etablering av Cladonia stellaris efter artificiell spridning i ej inhägnad skog i norra Sverige Renlav (främst Cladonia stellaris) spreds manuellt 2002 i en talldominerad skog i norra Sverige för att studera lavens etablering efter artificiell spridning. Försöksområdet var inte hägnat utan öppet för renbete. Laven spreds i intakt markvegetation på 1 m2-ytor, antingen i form av intakta lavbålar (0,25 m2) i ytans centrum eller som fragment över hela provytan. Lavens etablering följdes med hjälp av fotoinventering. År 2006, tre år efter första inventeringen, hade alla provytor betats av ren och lavens täckningsgrad hade reducerats betydligt. Vid inventeringen 2008 hade lavens täckningsgrad ökat med upp till 54% (intakt lav) resp. 88% (lavfragment), i jämförelse med täckningsgraden den första inventeringen. Mellan 2006 och 2008 ökade antalet fragment per provyta signifikant vilket indikerar en fortsatt naturlig etablering med spridning via fragment. Att sprida lav i form av intakta lavbålar förefaller mindre kostnadseffektivt än spridning av lav i fragmentform om spridningsområdet är öppet för renbete. Resultaten utgör ett stöd för hypotesen att artificiell spridning av renlav kan vara ett effektivt sätt att restaurera viktiga renbetesområden, även om området inte är skyddat för renbete.